Content analysis of the Brazilian scientific production on organic products (2010-2021) - Vilhena, Luciana Girão de; Braga, Francisco Laercio Pereira; Lima, Filipe Augusto Xavier (Science & Technology Journals, 2024)
The objective of this study was perform a content review on organic products in the Brazilian context between 2010 and 2021, from the perspective of the lexical analysis. In the methodological path, a survey was carried out for the national scientific works published on the Spell and CAPES journal platforms, in the delimited period, which made it possible to select 43 articles. Subsequently, the content of the selected articles was analyzed following a quantitative and qualitative approach, using the Iramuteq software. The results showed that the textual corpus was subdivided into classes from 1 to 4. As they cover complementary subjects, classes 2 and 3 are closer to each other, while classes 1 and 4 appear more independent and isolate. In general, important insights are noted, which emphasizes the need to encourage organic farming, in order to reduce pollution, promote sustainability, and address consumer’s environmental and health concerns. The results lead us to deduce that works and discussions related to organic products – which encompass the themes on sustainable development, public policies, and green/agroecological fairs – are still incipient in the family farming, which indicates the need for additional research to the literature.